Welcome Message from the General Co-Chair - Yves Lepage (My University, 2021)
in 1993 by Chulalongkorn University in Bangkok to the eleventh meeting hosted in 2016 by Thammasat university in Ayutthaya, the Symposium on Natural Language Processing (SNLP) was the bi-annual meeting to exchange idea, knowledge, and experience in the area of natural language processing (NLP) among researchers and experts from several countries in the world.
Keywords: Eleventh; null